The sex ratio and testosterone levels in tilapia immersed in different doses of 17α-methyltestosterone - Junior, Muhammad Zairin; Naufal, Muhammad Restya; Setiawati, Mia; Hardianto, Dian; Alimuddin, , (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
Tilapia fish farming using monosex male population has been reported to have 10% higher productivity compared to mix-sex culture. This study aimed to determine immersion dose of 17α-metiltestosterone (MT) that allowed higher male percentage, growth, survival, and measure testosterone level in fish body. The experiment was designed as three immersion doses, namely: 0; 1.8; and 5.4 mg/L MT, each with three replications. Immersion was conducted to 14-day-old larvae for four hours, with density of 100 fish/L of water. Testosterone levels in fish was measured using ELISA method, and sex identification was performed by histology method. The result showed that percentage of male fish was the same in the treatment of 1.8 mg/L and 5.4 mg/L, and 53–65% higher than the control without MT treatment (54% male). Growth and survival of fish until day 56 post immersion were the same. By ELISA analysis, the levels of testosterone in larvae just after immersion was similar in 1.8 mg/L and 5.4 mg/L treatments, decreased drastically on day 14 after immersion, and then the levels of testosterone to be similar with the control on day 28, i.e. about 2 ng/g. By PCR method with specific primer, sex reversed and normal males could be distinguished, and on day 71 the testosterone levels in sex reversed and normal males fish was also the same, 0.3 ng/g (P>0.05). Thus, sex reversal by immersion at a dose of 1.8 mg/L can be consider as a standard protocol for monosex tilapia production. Testosterone level in the body of MT-treated fish becomes the same to the control of less than one month post immersion